Effect of PbO on optical properties of tellurite glass - AlMokhtar Elazoumi, Salah Hassan; Abd. Aziz, Sidek; Rammah, Yasser S.; El-Mallawany, R.; Mohamed Kamari, Halimah; Matori, Khamirul Amin; Mohd Zaid, Mohd Hafiz (Elsevier, 2018)
Binary (1 − x)(TeO2) − x(PbO), x = 0, 0.10, 0.15, 0.20, 0.25, 0.30 mol% glass system was fabricated using melt quenching method. X-ray diffraction (XRD) technique was employed to confirm the amorphous nature. The microanalysis of the major components was performed using energy dispersive EDX and X-ray spectrometry. Both the molar volume and the density were measured. FTIR and UV spectra were recorded at 400–4000 cm–1 and 220–800 nm, respectively. The optical band gap (Eopt), Urbach’s energy (Eu), index of refraction (n) were calculated using absorption spectrum fitting (ASF) and derivation of absorption spectrum fitting (DASF) methods. Molar refraction Rm and molecular polarizability have been calculated according to (ASF) method.